Automated registration of optical coherence tomography and dermoscopy in the assessment of sub-clinical spread in basal cell carcinoma. (January 2014) - Coleman, A. J.; Penney, G. P.; Richardson, T. J.; Guyot, A.; Choi, M. J.; Sheth, N.; Craythorne, E.; Robson, A.; Mallipeddi, R.
Abstract Optical coherence tomography (OCT) has been shown to be of clinical value in imaging basal cell carcinoma (BCC). A novel dual OCT-video imaging system, providing automated registration of OCT and dermoscopy, has been developed to assess the potential of OCT in measuring the degree of sub-clinical spread of BCC. Seventeen patients selected for Mohs micrographic surgery (MMS) for BCC were recruited to the study. The extent of BCC infiltration beyond a segment of the clinically assessed pre-surgical border was evaluated using OCT. Sufficiently accurate (<0.5 mm) registration of OCT and dermoscopy images was achieved in 9 patients. The location of the OCT-assessed BCC border was also compared with that of the final surgical defect. Infiltration of BCC across the clinical border ranged from 0 mm to >2.5 mm. In addition, the OCT border lay between 0.5 mm and 2.0 mm inside the final MMS defect in those cases where this could be assessed. In one case, where the final MMS defect was over 17 mm from the clinical border, OCT showed >2.5 mm infiltration across the clinical border at the FOV limit. These results provide evidence that OCT allows more accurate assessment of sub-clinical spread of BCC than clinical observation alone. Such a capability may have clinical value in reducing the number of surgical stages in MMS for BCC. There may also be a role for OCT in aiding the selection of patients most suitable for MMS.